PERENCANAAN FILTER PASIF UNTUK MENINGKATKAN KUALITAS DAYA LISTRIK DI KAMPUS DIPLOMA III FAKULTAS TEKNIK UNDIP - Subari, Arkhan; Manan, Saiful (Vocational School Diponegoro University, 2014)
Arkhan Subari, Saiful Manan, in this paper explain that most electronic equipment is non-linear load. Likewise with the equipment in campus buildings Diploma III Faculty of Engineering. Non-linear load is a load that has a voltage waveform supplied from non sinusiodal although sinusoidal voltage. Non-sinusoidal wave causes the shape of the voltage becomes distorted or defects that result in decreased quality of power. The defect wave called harmonics. To dampen harmonics on non-linear load can be used filter. With the addition of a filter on the power system, then the waves of unwanted harmonics can be suppressed as small as possible. In addition, harmonic filter at the fundamental frequency can compensate for reactive power and is used to improve the power factor of the system. From the measurement results in the Diploma Program Campus FT Undip found that the influence of harmonic waves big enough. THDv reached 32.13% while the THDi amounted to 7.85%. It affects so cos phi cos phi measured just 0.72. After the installation of a passive filter, the value THDv and THDi be good lebik ie 1.61% and 0.39% to reach 0.94 cos phi measured. Key word: non-linear loads, non-sinusoidal waveform, harmonics, power factor, filter LC